2021
DOI: 10.1002/admi.202100197
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Surface N‐Doping of Fe‐N‐C Catalysts Derived from Fe/Melamine‐Decorated Polyaniline for Oxygen Reduction Electrocatalysis

Abstract: The insufficient active site density and poor stability of iron and nitrogen co‐doped carbon (Fe‐N‐C) catalyst remain as great challenges for advanced oxygen reduction reaction (ORR). Surface N‐doping together with Fe species is considered as an efficient strategy to enhance the catalytic activity and stability of Fe‐N‐C. Here, we report a facile preparation of high performing Fe‐N‐C catalysts derived from Fe/melamine‐decorated polyaniline. The optimal catalyst displays much better ORR onset and half‐wave pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 49 publications
(79 reference statements)
1
9
0
Order By: Relevance
“…The four types of nitrogen are supposed to provide stability to the synthesized electrocatalyst. 1,28,32 The shiing of the d-band centre of FeO x downward to compensate for the distortion caused as a result of electronic interaction with cobalt oxides (CoO x ) and nitrogens is in agreement with the dband centre model. Enhanced electrocatalytic activity of the FeO x @CoO x /NC2 electrocatalyst is attributed to the cumulative electronic interaction of cobalt, iron and nitrogen sites, thereby modulating the chemisorption energy of O 2 and the reaction mechanism.…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…The four types of nitrogen are supposed to provide stability to the synthesized electrocatalyst. 1,28,32 The shiing of the d-band centre of FeO x downward to compensate for the distortion caused as a result of electronic interaction with cobalt oxides (CoO x ) and nitrogens is in agreement with the dband centre model. Enhanced electrocatalytic activity of the FeO x @CoO x /NC2 electrocatalyst is attributed to the cumulative electronic interaction of cobalt, iron and nitrogen sites, thereby modulating the chemisorption energy of O 2 and the reaction mechanism.…”
Section: Resultssupporting
confidence: 75%
“…35 The superior catalytic activity and stability of FeO x @CoO x /NC2 can be attributed to the following key points. (1) Strong synergism between FeO x , CoO x and four types of nitrogen in nitrogendoped tubular carbon; (2) the introduction of four types of nitrogen as a result of decomposition of 1,10-phenanthroline induces uneven charge distribution in the carbon matrix, greatly facilitating the charge transfer; (3) greater number of active sites and exposed surface area of the synthesized electrocatalyst. 35 To assess the efficiency of the catalyst, all the electrochemical results were compared to those of commercial Pt/C under the same experimental conditions.…”
Section: Electrochemical Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The comparison between the control material PANI-TS-TC ( Figure 5 a1,a2) and those containing the metallic species PANI-Ni-TS-TC ( Figure 5 b1,b2) and PANI-Co-TS-TC ( Figure 5 c1,c2) shows the presence of micro-structured particles of different shape and size. For polyaniline-based materials, it is known that the thermal treatment under an inert atmosphere of argon or nitrogen at 600–1200 °C will trigger the rearrangement of the different atoms to create new bonds of carbon–carbon (C-C, C=C, C-H) and carbon–nitrogen (pyridinic-N, pyrrolic-N, and graphitic-N) in a nanostructured network that has different levels of electrical conductivity, number of active sites and electrocatalytic kinetics [ 18 , 20 , 54 , 55 , 56 , 57 , 58 ]. In order to obtain a qualitative analysis of the nature of the structures formed with metallic species, in-depth analysis was conducted by EDX.…”
Section: Resultsmentioning
confidence: 99%
“…30 It is found that the graphitization degree, porosity and conductivity of Fe/N/C catalysts are effectively improved by introducing melamine in the preparation process. [31][32][33] Besides, it can be seen that using melamine as ligand to prepare catalysts can signicantly enhance the ORR catalytic performance. 34 Most of these catalysts pyrolyze at high temperature, various active substances are produced besides the Fe-N x coordination active site, such as metallic Fe/Fe 3 C nanoparticles, Fe x O y or FeN x nanoparticles and so on.…”
Section: Introductionmentioning
confidence: 99%